IL15 Enhances CAR-T Cell Antitumor Activity by Reducing mTORC1 Activity and Preserving Their Stem Cell Memory Phenotype - Alizadeh, Darya; Wong, Robyn A; Yang, Xin; Wang, Dongrui; Pecoraro, Joseph R; Kuo, Cheng-Fu; Aguilar, Brenda; Qi, Yue; Ann, David K; Starr, Renate; Urak, Ryan; Wang, Xiuli; et al. (Cancer immunology research, 2019)
Improvements in the quality and fitness of chimeric antigen receptor (CAR)-engineered T cells, through CAR design or manufacturing optimizations, could enhance the therapeutic potential of CAR-T cells. One parameter influencing the effectiveness of CAR-T cell therapy is the differentiation status of the final product: CAR-T cells that are less-differentiated and less exhausted are more therapeutically effective. In the current study, we demonstrate that CAR-T cells expanded in IL15 (CAR-T/IL15) preserve a less-differentiated stem cell memory (Tscm) phenotype, defined by expression of CD62L CD45RA CCR7 , as compared with cells cultured in IL2 (CAR-T/IL2). CAR-T/IL15 cells exhibited reduced expression of exhaustion markers, higher antiapoptotic properties, and increased proliferative capacity upon antigen challenge. Furthermore, CAR-T/IL15 cells exhibited decreased mTORC1 activity, reduced expression of glycolytic enzymes and improved mitochondrial fitness. CAR-T/IL2 cells cultured in rapamycin (mTORC1 inhibitor) shared phenotypic features with CAR-T/IL15 cells, suggesting that IL15-mediated reduction of mTORC1 activity is responsible for preserving the Tscm phenotype. CAR-T/IL15 cells promoted superior antitumor responses in comparison with CAR-T/IL2 cells. Inclusion of cytokines IL7 and/or IL21 in addition to IL15 reduced the beneficial effects of IL15 on CAR-T phenotype and antitumor potency. Our findings show that IL15 preserves the CAR-T cell Tscm phenotype and improves their metabolic fitness, which results in superior antitumor activity, thus opening an avenue that may improve future adoptive T-cell therapies.